Severe Spinal Cord Injury in Rats Induces Chronic Changes in the Spinal Cord and Cerebral Cortex Metabolism, Adjusted by Thiamine That Improves Locomotor Performance - Boyko, Alexandra; Tsepkova, Polina; Aleshin, Vasily; Artiukhov, Artem; Mkrtchyan, Garik; Ksenofontov, Alexander; Baratova, Lyudmila; Ryabov, Sergey; Graf, Anastasia; Bunik, Victoria (Frontiers in Molecular Neuroscience, 2021)
Our study aims at developing knowledge-based strategies minimizing chronic changes in the brain after severe spinal cord injury (SCI). The SCI-induced long-term metabolic alterations and their reactivity to treatments shortly after the injury are characterized in rats. Eight weeks after severe SCI, significant mitochondrial lesions outside the injured area are demonstrated in the spinal cord and cerebral cortex. Among the six tested enzymes essential for the TCA cycle and amino acid metabolism, mitochondrial 2-oxoglutarate dehydrogenase complex (OGDHC) is the most affected one. SCI downregulates this complex by 90% in the spinal cord and 30% in the cerebral cortex. This is associated with the tissue-specific changes in other enzymes of the OGDHC network. Single administrations of a pro-activator (thiamine, or vitamin B1, 1.2 mmol/kg) or a synthetic pro-inhibitor (triethyl glutaryl phosphonate, TEGP, 0.02 mmol/kg) of OGDHC within 15-20 h after SCI are tested as protective strategies. The biochemical and physiological assessments eight weeks after SCI reveal that thiamine, but not TEGP, alleviates the SCI-induced perturbations in the rat brain metabolism, accompanied by the decreased expression of (acetyl)p53, increased expression of sirtuin 5 and an 18% improvement in the locomotor recovery. Treatment of the non-operated rats with the OGDHC pro-inhibitor TEGP increases the p53 acetylation in the brain, approaching the brain metabolic profiles to those after SCI. Our data testify to an important contribution of the OGDHC regulation to the chronic consequences of SCI and their control by p53 and sirtuin 5.